Bis(propan-2-yl) [(2S,3S)-2-hydroxy-3-nitrobutan-2-yl]phosphonate - Mandal, T.; Samanta, S.; Broker, G.A.; Zhao, C.G.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the title compound, C(10)H(22)NO(6)P, a staggered conformation is found when the molecule is viewed down the central P-C bond, with the oxo and hydroxy groups gauche to each other. The crystal structure features supramolecular chains of helical topology propagating along the b axis, mediated by O-H center dot center dot center dot O hydrogen bonds.